In Search of the Cause of Violence in Edgar Allen Poe’s “The Black Cat” - Alhmdni, Thulfiqar Abdulameer Sulaiman (International Journal of Psychosocial Rehabilitation, 2020)
This paper aims to shed light on the blurring characterization and the prevailing paradox in Edgar Allen Poe’s short story, ’’The Black Cat.’’ In his critical essay, ’’The Philosophy of Composition,’’ Poe emphasized the significance of creating unity or totality of effect in his stories which is in contrast with Modernist short story writers and novelists’ elliptical and suggestive technique whose major stress is on ‘open-endedness’ of a work of art. The totality or the main concept he intends to achieve in this short story is the same as the one in ’’The Cask of Amontillado,’’ and ’’The Tell-Tale Heart,’’ and this concept is violence. Notwithstanding his teleological style, this study intends to show that the end of the story not elucidating the sociological and political side influencing the character, and his perversity which is shown to stem from a superstition, and surprisingly the text which contributes to the reality of the superstition at the end of the story, makes this story more suggestive than what he had aimed for. By taking into consideration the historical, sociological, and biographical context of Poe himself, this study attempts to find a reason behind this violence; this recourse to contexts in which Poe was in is due to the lack of narrator’s background, and at the same time, it analyzes the characters’ personality through some images using Lacan’s Psychoanalysis, and also Zizek’s analysis of the concept of “Violence.”.